Sexuality - Bristow, Joseph (Routledge, 1997)
Joseph Bristow introduces readers to the most influential contemporary theories of sexual desire and reveals how nineteenth century scientists invented 'sexuality'. This clear and fascinating introductory guide makes complex theoretical ideas accessible to readers of all levels. It explores: